Progress and recent trends in microbial fuel cells - Kundu, Patit P.; Dutta, Kingshuk (Elsevier, 2018)
Progress and Recent Trends in Microbial Fuel Cells provides an in-depth analysis of the fundamentals, working principles, applications and advancements (including commercialization aspects) made in the field of Microbial Fuel Cells research, with critical analyses and opinions from experts around the world. Microbial Fuel cell, as a potential alternative energy harnessing device, has been progressing steadily towards fruitful commercialization. Involvements of electrolyte membranes and catalysts have been two of the most critical factors toward achieving this progress. Added applications of MFCs in areas of bio-hydrogen production and wastewater treatment have made this technology extremely attractive and important.